2019
DOI: 10.1002/lary.27831
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of three‐dimensional printing in otolaryngology–head and neck surgery: A systematic review

Abstract: Objectives Medical three‐dimensional (3D) printing, the fabrication of handheld models from medical images, has the potential to become an integral part of otolaryngology–head and neck surgery (Oto‐HNS) with broad impact across its subspecialties. We review the basic principles of this technology and provide a comprehensive summary of reported clinical applications in the field. Methods Standard bibliographic databases (MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 60 publications
(111 reference statements)
0
58
0
Order By: Relevance
“…In our view, computational fluid dynamic models with parameters of mucosal surfaces and the technology of 3D bioprinting, which could not only highly simulate the live mucosa but also avoid the potential ethical issue in a human study, are promising for solving the problem. [26][27][28] In addition, the small population in the drug distribution study using three sinonasal models was another limitation. Therefore, triplicate experiments were conducted to compensate for the small sample size to some degree, and the effect sizes showed that the differences we observed were significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our view, computational fluid dynamic models with parameters of mucosal surfaces and the technology of 3D bioprinting, which could not only highly simulate the live mucosa but also avoid the potential ethical issue in a human study, are promising for solving the problem. [26][27][28] In addition, the small population in the drug distribution study using three sinonasal models was another limitation. Therefore, triplicate experiments were conducted to compensate for the small sample size to some degree, and the effect sizes showed that the differences we observed were significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the physiological characteristics of the mucosa and mucociliary transport could not be mimicked using 3D printed models, the initial range of the aerosol deposition reflected by the staining still offered valuable information for decision‐making in clinical work and device innovation. In our view, computational fluid dynamic models with parameters of mucosal surfaces and the technology of 3D bioprinting, which could not only highly simulate the live mucosa but also avoid the potential ethical issue in a human study, are promising for solving the problem 26‐28 . In addition, the small population in the drug distribution study using three sinonasal models was another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of institutions have moved to internal RP production to mitigate the cost and time required in formal VSP [32] . The 3D printer equipment costs have been estimated as minimal as $1000 USD with material costs for printing these models reaching $1 USD and 4-5 h of printing time required per application [32] . This has expanded the usage of RP in many medical centers and allowed for increasing research and educational applications in head and neck reconstruction.…”
Section: Rapid Prototyping For Head and Neck Reconstructionmentioning
confidence: 99%
“…Three‐dimensional (3D) printing has become popular as we move towards personalizing medicine. Its utility expands constantly as we discover novel ways to implement this technology, even within our own field 7 . Within head and neck oncology, the reported utilization of this technology largely relates to surgical planning 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Its utility expands constantly as we discover novel ways to implement this technology, even within our own field 7 . Within head and neck oncology, the reported utilization of this technology largely relates to surgical planning 7 . This case report describes a scenario in which a patient‐specific 3D printed fistula plug was used as a bridging therapy before definitive management of pharyngocutaneous fistulae.…”
Section: Introductionmentioning
confidence: 99%